Desain Pembelajaran Garis dan Sudut Menggunakan Jam Dinding Lingkaran untuk Siswa SMP Kelas VII - Ajeng Ramadhani; Rully Charitas Indra Prahmana (Department of Mathematics Education, Faculty of Tarbiyah and Teacher Training, UIN Sunan Ampel Surabaya, 2019)
The purpose of this research is to understanding the role of line and angle learning design in students’ comprehension of mathematical concept and also to understanding the students’ learning result through LAS (Lembar Aktivitas Mahasiswa) or student activity paper that is based on the Indonesian Realistic Mathematics Education approach. The research method used in this research is design research. The result of this research shows that the activity of using props or drawing a clock circle could motivate the students in checking out the shaped angle, So the students will have the idea to calculate how big is the angle that is shaped by the clockwise and also to determine its types. So, the design that is used could help the students to understanding the concept of angle through the context of clock circle.